Urban flood regulating ecosystem services under climate change: how can Nature-based Solutions contribute? - Wübbelmann, Thea; Förster, Kristian; Bouwer, Laurens M.; Dworczyk, Claudia; Bender, Steffen; Burkhard, Benjamin (Frontiers in Water, 2023)
Urban areas are mostly highly sealed spaces, which often leads to large proportions of surface runoff. Simultaneously, heavy rainfall events are projected to increase in frequency and intensity with global climate change. Consequently, higher risks and damages from pluvial flooding can be expected. With the analysis of Flood Regulating Ecosystem Services (FRES), the benefits from nature to people to reduce surface runoff and runoff peaks can be determined. However, urban FRES are rarely studied for heavy rainfall events under changing climate conditions. Therefore, we first estimate the functionality of current urban FRES-supply and demand under changing climate conditions. Secondly, we identify the effects of nature-based solutions (NBS) on FRES-supply and demand and their potential future functionality and benefits concerning more intensive rainfall events. A district of the city of Rostock serves as the case study area. Besides the reference conditions based on the current land use, we investigate two potential NBS: 1) increasing the number of trees; and 2) unsealing and soil improvement. Both NBS are applied for three heavy rainfall events. Besides a reference scenario, two future scenarios were developed to investigate the ecosystem service functionality, based on 21% and 28% more intense rainfall. While the potential FRES-demand was held constant, we assessed the FRES-supply and actual demand for all scenario combinations, using the hydrological model LEAFlood. Comparing the actual demand and supply indicates the changes in FRES-supply surplus and unmet demand increase. Using FRES indicators from hydrological models to estimate future functionality under changing climate conditions and the benefits of NBS can serve as an analysis and decision-support tool for decision-makers to reduce future urban flood risk. In the next step, different scenarios for flood regulation demand and other adaptation measures can be tested with practical applications in other urban areas.